1988
DOI: 10.1088/0029-5515/28/3/014
|View full text |Cite
|
Sign up to set email alerts
|

Fast ion ripple losses during neutral injection in TFR

Abstract: Fast ion ripple losses during neutral beam injection in TFR are measured near-quantitatively with an array of Faraday collectors mounted between two toroidal field coils. The collected currents show multiple evidence for fast ion ripple losses and correspond to global losses of 30-40% of the injected current. The measurements are complemented by a simple Fokker-Planck model, itself checked against Monte Carlo simulations on several cases. These calculations clarify many experimental features but predict only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…In TFR, the slowing-down spectrum of perpendicular beam ions was strongly depleted, in rough agreement with calculated losses associated with ripple trapping [26]. In ALCATOR C, the heating efficiency during lower hybrid [270] The Faraday cup current scaled approximately linearly with beam power and was largest for the detector situated -7 cm from the centre of the coil, as expected for ripple losses [271]. The measured current was about twice as large as that theoretically expected, however.…”
Section: Toroidal Field Ripplesupporting
confidence: 59%
“…In TFR, the slowing-down spectrum of perpendicular beam ions was strongly depleted, in rough agreement with calculated losses associated with ripple trapping [26]. In ALCATOR C, the heating efficiency during lower hybrid [270] The Faraday cup current scaled approximately linearly with beam power and was largest for the detector situated -7 cm from the centre of the coil, as expected for ripple losses [271]. The measured current was about twice as large as that theoretically expected, however.…”
Section: Toroidal Field Ripplesupporting
confidence: 59%
“…Fast-ion ripple loss arises from two major processes: ripple-trapped loss and banana drift loss. The first quantitative measurements on ripple-trapped loss were performed in TFR [11], and it was reported that many experimental features were consistent with the calculations, but the observed ripple loss was twice as large as the calculated one.…”
mentioning
confidence: 65%
“…The latter is a "confined" alpha which can be collected by the detector when the aperture is far enough inward, even without any radial diffusion of the orbit. 29. Qualitative picture of the effects of limiter shadowing on the alpha detection in this experiment.…”
mentioning
confidence: 90%